Mutagenicity of cytostatic drugs in a bacterial system. II. DNA-repair test - Marhan, J (Folia microbiologica, 1995)
A liquid micromethod modification of the DNA-repair test using an automatic growth analyzer was developed. The wild strain Escherichia coli WP2 and six repair-deficient isogenic test strains were used. To compare this repair test with the conventional plate Ames test, a set of nine cytostatics were tested. Cloturin, adriamycin, mitoxantron, oracin, lomustine and tris(2-chloroethyl)amine were found to be positive, and 6-mercaptopurine, butocin and cyclophosphamide negative. The experimental micromethod appears to be useful for assessing the differential lethality in bacteria and can be combined in any short-term test system to predict genotoxicity.
Keywords: Drug Screening Assays, Antitumor; DNA Repair; protinádorové látky; poškození DNA; oprava DNA; screeningové testy protinádorových léčiv; DNA bakterií; DNA Damage; Mutagenicity Tests; Escherichia coli; Antineoplastic Agents; testy genotoxicity; DNA, Bacterial